INTELLECTUAL CAPITAL PADA ECONOMIC VALUE ADDED - Adelia Salsabilah; Esti Damayanti (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This research was conducted at Food and Beverage Subsector Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2023 period. The research method used is descriptive quantitative research with the data used in the form of secondary data obtained from the Indonesian Stock Exchange. The sample determination method used a purposive sampling method totalling 26 companies that met the research criteria. Based on the results of this research analysis, it can be seen that partially the Human Capital Efficiency variable has a positive and significant effect on Economic Value Added, Structural Capital Efficiency has a negative and insignificant effect on Economic Value Added and Capital Employed Efficiency has a positive and insignificant effect on Economic Value Added. This research is expected to provide information related to Economic Value Added (EVA) to investor management, shareholders and related parties regarding financial reports to make it easier to determine strategies so that there are no mistakes in decision making.